Factors Affecting the Implementation of Early Initiation of Breastfeeding (IMD) in Postpartum Mothers at RSUD Dr. Kanujoso Djatiwibowo Balikpapan - Ni Nyoman Murti; Naomi Isabella Hutabarat (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Early initiation of breastfeeding (IMD) is a crucial process that allows newborns to begin breastfeeding within the first hour after birth. This practice strengthens the mother-child bond, enhances the baby’s immune system, and reduces neonatal mortality. Despite its benefits, IMD implementation in Indonesia still encounters various challenges, and few studies have examined its influencing factors by region or facility. This study aims to identify the factors associated with IMD implementation among postpartum mothers at RSUD Dr. Kanujoso Djatiwibowo Balikpapan. A descriptive analytic design with a cross-sectional approach was used. The study involved 42 postpartum mothers selected through non-probability saturated sampling. Data collection was conducted using questionnaires, and the results were analyzed with univariate and bivariate methods using the Chi-Square test. A total of 61.9% of respondents practiced IMD. Most had good knowledge (64.3%), belonged to the risk parity group (52.2%), received family support (54.8%), and had support from health workers (57.1%). Significant relationships were found between IMD implementation and maternal knowledge (p = 0.033), family support (p = 0.017), and health worker support (p = 0.003). These findings suggest the importance of education and support to improve IMD practices. In conclusion, IMD implementation is significantly influenced by maternal knowledge, family involvement, and healthcare provider support. Strengthening educational and support interventions is essential to enhance IMD coverage in health facilities.